Pluralising pasts : heritage, identity and place in multicultural societies - Ashworth, G. J. (Gregory John); Graham, B. J. (Brian J.); Tunbridge, J. E. (Pluto Press, 2007)
"The heritage industry is big business. From museums and the preservation of old buildings to broader questions of community and identity, heritage is now a political issue. This book explores what heritage means and how it is used to encourage people to identify with particular places and "traditions." The authors show how contemporary societies use heritage in the creation and management of collective identities and, most especially, the different ways in which it is involved with the questions of multicultural societies. The resources that are poured into heritage mean that questions of identity are widely discussed at a policy level: what does it mean to be American or British, or a minority in any society? This book shows how heritage is used commercially and politically to shape the ways people represent themselves, and are represented, in diverse and hybrid societies." http://www.loc.gov/catdir/enhancements/fy0812/2008271647-d.html